An Analyzer of Computer Network Logs Based on Paraconsistent Logic - Pimenta, Avelino Palma [UNESP]; Abe, Jair Minoro [UNESP]; Oliveira, Cristina Correa de [UNESP]; Umeda, S.; Nakano, M.; Mizuyama, H.; Hibino, H.; Kiritsis, D.; VonCieminski, G. (Springer, 2015)
In recent years, the network vulnerability events draw the attention to the issue of the information management on the World Wide Web. The detected vulnerability was not only restricted to individuals, but also to enterprises and governments. Over the past decade, networks have become an affordable way for several computer services, but also a major challenge for network managers to maintain its operation. The main problem is the difficulty to deal with big amount of data generated by user requests, which in turn ultimately generate increasing information logs. Moreover, the dynamics of the services can lead to detect false positive and negative ones, so uncertainty is a theme to be considered. The employment of classical logic may not be adequate to solve problems of this nature. The aim of this paper is to present the development of a Paraconsistent analyzer, in order to extract some computer networks patterns of interest.
Keywords: Paraconsistent logic; Computer networks; Pattern recognition; Decision-making